The given equation is expressed as
y = - 3x^2
The first step is to substitute values of x into the equation and find corresponding values of y. We have
For x = - 3, y = - 3(- 3)^2 = - 3 * 9 = - 27
For x = - 2, y = - 3(- 2)^2 = - 3 * 4 = - 12
For x = - 1, y = - 3(- 1)^2 = - 3 * 1 = - 3
For x = 0, y = - 3(0)^2 = - 3 * 0 = 0
For x = 1, y = - 3(1)^2 = - 3 * 1 = - 3
For x = 2, y = - 3(2)^2 = - 3 * 4 = - 12
For x = 3, y = - 3(3)^2 = - 3 * 9 = - 27
Thus, the corresponding x and y coordinates that would be plotted on the graph are
(- 3, - 27)
(- 2, - 12)
(- 1, - 3)
(0, 0)
(1, - 3)
(2, - 12)
(3, - 27)
The graph is shown below